Backswitching effect in relaxor SBN crystals, studied by PFM-spectroscopy. Issue 4 (2nd November 2017) - Simagina, L. V.; Volk, T. R.; Bodnarchuk, Ya. V.; Gainutdinov, R. V.; Ivleva, L. I.
ABSTRACT: We present studies of local piezoelectric hysteresis loops Hω -UDC (PFM spectroscopy method) measured in SBN crystals under square pulse trains. The dependences of the loop height, i. e., of the remnant polarization Pr, on the pulse duration tp and spacing Δt were found at tp < 1000 ms. The effects are pronounced at tp /Δt < 1, which permits us to attribute them to backswitching. For the first time, the dependence of coercive fields on Δt was revealed, which as well as the backswitching is caused by Pr instability.